2005
DOI: 10.1097/01.brs.0000192208.66360.29
|View full text |Cite
|
Sign up to set email alerts
|

Acute Intracranial Subdural Hematoma Following a Lumbar CSF Leak Caused by Spine Surgery

Abstract: We report the rare case of an acute intracranial subdural hematoma caused by a CSF leak following lumbar surgery. This report illustrates the potential morbidity associated with CSF leaks occurring after spinal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
81
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 15 publications
0
81
1
2
Order By: Relevance
“…Previous studies have shown that subdural hematoma may result from stretching and tearing of the bridging vein between the dura and cerebral hemispheres in cases of excessive CSF drainage or shrinkage of the brain due to dehydration. 9,10) In our case, we suspected that sudden drops in CSF pressure at the insertion of CSF drainage, and not excessive CSF drainage, might be the cause of intracranial hypotension and rupture of the cortical veins, however, the pressure of CSF was continued 10 mmHg (13.5 cm H2O) during and after the operation. Although the bleeding may have occurred just after the insertion, the hemorrhagic space was only limited at very narrow space of sagittal sinus region because CSF drainage tube that was closed just after insertion before 24 hours of systemic heparinization and the pressure of CSF was continuously kept at 10 mmHg (13.5 cm H2O) during the operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that subdural hematoma may result from stretching and tearing of the bridging vein between the dura and cerebral hemispheres in cases of excessive CSF drainage or shrinkage of the brain due to dehydration. 9,10) In our case, we suspected that sudden drops in CSF pressure at the insertion of CSF drainage, and not excessive CSF drainage, might be the cause of intracranial hypotension and rupture of the cortical veins, however, the pressure of CSF was continued 10 mmHg (13.5 cm H2O) during and after the operation. Although the bleeding may have occurred just after the insertion, the hemorrhagic space was only limited at very narrow space of sagittal sinus region because CSF drainage tube that was closed just after insertion before 24 hours of systemic heparinization and the pressure of CSF was continuously kept at 10 mmHg (13.5 cm H2O) during the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Moderately small amounts of subdural blood did not result in neurologic deficit, and headache is a well-known result of procedures that reduce spinal fluid volume and pressure. 10) In our patient, the CSF drainage volume after 24 hours was only 125 mL; however, SDH may have resulted from the CSF drainage. Frequent neurological checks are imperative after CSF drainage catheter insertion.…”
Section: Discussionmentioning
confidence: 99%
“…One of the known complications of intrathecal drug delivery system is cerebrospinal fluid (CSF) leak due to a dural puncture during placement of an intrathecal catheter [4]. The reduction of CSF volume and pressure may lead to intracranial hypotension, and manifest as positional headaches.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple intracranial hemorrhages have been reported in 5 cases after spinal surgery, although single hemorrhage was recognized in 7 cases. 3,4,6,[9][10][11][12] Risk factors for non-traumatic intracranial hemorrhages, such as hypertension and coagulopathy, are always considered as potential causes of postoperative bleeding. 14) Rapid reduction of ICP might be key in the development of intracranial hemorrhages after spinal sur-Neurol Med Chir (Tokyo) 52, September, 2012…”
Section: Discussionmentioning
confidence: 99%